Effects of nocturnal light exposure on circadian rhythm and energy metabolism in healthy adults: A randomized crossover trial. (3rd April 2022) - Choi, Youngju; Nakamura, Yuki; Akazawa, Nobuhiko; Park, Insung; Kwak, Hyo-Bum; Tokuyama, Kumpei; Maeda, Seiji
ABSTRACT: Exposure to continuous light at night, including night-shift work or a nocturnal lifestyle, is emerging as a novel deleterious factor for weight gain and obesity. Here, we examined whether a single bout of bright light (BL) exposure at night affects energy metabolism via changes in circadian rhythm and nocturnal melatonin production. Ten healthy young men were randomized to a two-way crossover experimental design protocol: control (< 50 lux) and BL (approximately 10000 lux) conditions, with at least seven days of interval. The participants were exposed to each condition for 3 h (21:00–24:00) before sleep (0 lux, 00:00–07:00) in a room-type metabolic chamber. On each experimental night (21:00–07:00), energy expenditure, respiratory quotient (RQ), and substrate oxidation were measured to determine the energy metabolism. BL exposure prior to bedtime altered biological rhythms, disrupted the nocturnal decline in body temperature, and suppressed the melatonin level before sleeping, resulting in an increase in sleep latency. Indirect calorimetry data revealed that BL exposure significantly decreased the fat oxidation and increased the RQ, an indicator of the carbohydrate-to-fat oxidation ratio, throughout the whole period (light exposure and sleep). We revealed that acute BL exposure prior to bedtime exacerbated circadian rhythms and substrate oxidations, suggesting that chronic BL exposure at night may lead to obesity risk due to disturbances in circadian rhythms and macronutrient metabolism.